Academic Concerns of International Students in the US - Cody J Perry; Jennifer Weatherford; David Lausch (Adult Education Research Conference, 2016)
Our purpose was to identify specific academic concerns among international students. Sixty-three international students completed the self-report survey. It was found that most academic concerns centered on faculty and advisers.
Keywords: International students; academics; faculty support